PERANCANGAN MEDIA PROMOSI WANA WISATA PANTAI PLENGKUNG BANYUWANGI SEBAGAI UPAYA MENINGKATKAN DAYA TARIK WISATAWAN - Widodo, Kennedy Rony Dewantara; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal ArtNouveau, 2013)
The goal of this media promotion design is to increase tourist attraction against the potential of plengkung beach. This media promotion design using qualitative method researchfor determining the design concept. Collecting data obtained through observation in order to determine the appropriate media selection for the application, the interview in order to obtain detailed information from competent sources, the literature in order to obtain the literature to support the design, and documentation in order for the material design.Through analysis of collected data was found one big idea for theme design. Big idea is a unforgetable sensation, this big idea describe the adventure on plengkung beach and word sensation in this big idea is a adventure sensation.Then, after big idea was found, design was created and followed by the manufacture of promotional media.Results of this media promotion design expected to help increase tourist attraction on plengkung beach.